Phylogenèse et psychogenèse de l'écrit : l'utilisation fonctionnelle et raisonnement dans un exemple en mathématiques - EIRINI MATALLIOTAKI (Metaichmio Publications, 2009)
This article proposes to examine the relations between writing and cognition starting from work in cognitive anthropology (Goody and Olson primarily). The conditions of the emergence of the new functions of the human spirit compared to the production and to the use of graphic systems are discussed. We draw the particular characteristics of the writing and its use, the immediate cognitive possibilities that derive from it as well as the cognitive consequences in the long run. We also examine the theoretical aspects on the writing as a graphical representation in a process of psychogenesis. We explore the bond that exists between psychogenesis and phylogenesis with regard to the writing. We also examine empirically the conditions and the potential functional use that young children can make of graphic representations for problem resolving in mathematics.